Assessment of Cihampelas River Water Quality Status using STORET Method and Pollution Index - Aiman Ibrahim; Muhamad Suhaemi Syawal; Achmad Sjarmidi; Siti Aisyah; Sugiarti Sugiarti; Aldiano Rahmadya; Agus Waluyo (Universitas Diponegoro, 2023)
The Cihampelas River is one of river that crosses the Regency and City of Bandung, West Java, with a length of 8.5 km. This study aims to assess the water quality status of Cihampelas River based on the STORET method and Pollution Index. The research was conducted at four stations based on the level of anthropogenic activity from July to September 2016. Measurements of the physical and chemical parameters of the waters were carried out five times at two-week intervals. Water quality status was assessed using the STORET method and Pollution Index based on the parameters TDS, TSS, pH, DO, BOD, COD, nitrate, nitrite, ammonia, and total phosphorus (TP). Using the STORET method, shows a score of -20 to -46 in the category of moderately to severely polluted waters. Based on the Pollution Index method, the waters of the Cihampelas River show lightly to severely polluted conditions with a score of 1.14 to 44.66. The water quality status of the Cihampelas River shows a decreasing trend from the upstream to the downstream.